Characterization of inulolytic enzymes from the Jerusalem artichoke-derived Glutamicibacter mishrai NJAU-1 - TOKSOY ÖNER, EBRU (My University, 2022)
The rhizosphere context of inulin-accumulating plants, such as Jerusalem artichoke (Helianthus tuberosus), is an ideal starting basis for the discovery of inulolytic enzymes with potential for bio fructose production. We isolated a Glutamicibacter mishrai NJAU-1 strain from this context, showing exo-inulinase activity, releasing fructose from fructans. The growth conditions (pH 9.0; 15 degrees C) were adjusted, and the production of inulinase by Glutamicibacter mishrai NJAU-1 increased by 90% (0.32 U/mL). Intriguingly, both levan and inulin, but not fructose and sucrose, induced the production of exo-inulinase activity. Two exo-inulinase genes (inu/ and inu2) were cloned and heterologously expressed in Pichia pastoris. While INU2 preferentially hydrolyzed longer inulins, the smallest fructan 1-kestose appeared as the preferred substrate for INU1, also efficiently degrading nystose and sucrose. Active site docking studies with GFn- and Fn-type small inulins (G is glucose, F is fructose, and n is the number of beta (2-1) bound fructose moieties) revealed subtle substrate differences between INU1 and INU2. A possible explanation about substrate specificity and INU\"s protein structure is then suggested.
Keywords: Yaşam Bilimleri; Biyoteknoloji; Temel Bilimler; Life Sciences; Biotechnology; Natural Sciences; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; Mikrobiyoloji; Yaşam Bilimleri (LIFE); BIOTECHNOLOGY & APPLIED MICROBIOLOGY; MICROBIOLOGY; Life Sciences (LIFE); Uygulamalı Mikrobiyoloji ve Biyoteknoloji; Moleküler Tıp; Applied Microbiology and Biotechnology; Molecular Medicine; Bio fructose; Exo-inulinase; Glutamicibacter mishrai; Fructan; Jerusalem artichoke; TOLERANT EXO-INULINASE; MICROBIAL INULINASES; EXTRACELLULAR EXOINULINASE; PURIFICATION; CLONING; EXPRESSION; ARTHROBACTER; HYDROLYSIS; FRUCTOSE; CHICORY